Bioactivity Performance of Pure Mg after Plasma Electrolytic Oxidation in Silicate-Based Solutions - Husak, Y.; Michalska, J.; Oleshko, O.; Korniienko, V.; Grundsteins, K.; Dryhval, B.; Altundal, S.; Mishchenko, O.; Viter, R.; Pogorielov, M.; Simka, W.; Міщенко, Олег Миколайович (My University, 2021)
Abstract: The biodegradable metals, including magnesium (Mg), are a convenient alternative to permanent metals but fast uncontrolled corrosion limited wide clinical application. Formation of a barrier coating on Mg alloys could be a successful strategy for the production of a stable external layer that prevents fast corrosion. Our research was aimed to develop an Mg stable oxide coating using plasma electrolytic oxidation (PEO) in silicate-based solutions. 99.9% pure Mg alloy was anodized in electrolytes contained mixtures of sodium silicate and sodium fluoride, calcium hydroxide and sodium hydroxide. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), contact angle (CA), Photoluminescence analysis and immersion tests were performed to assess structural and long-term corrosion properties of the new coating. Biocompatibility and antibacterial potential of the new coating were evaluated using U2OS cell culture and the grampositive Staphylococcus aureus (S. aureus, strain B 918). PEO provided the formation of a porous oxide layer with relatively high roughness. It was shown that Ca(OH)2 was a crucial compound for oxidation and surface modification of Mg implants, treated with the PEO method. The addition of Ca2+ ions resulted in more intense oxidation of the Mg surface and growth of the oxide layer with a higher active surface area. Cell culture experiments demonstrated appropriate cell adhesion to all investigated coatings with a significantly better proliferation rate for the samples treated in Ca(OH)2- containing electrolyte. In contrast, NaOH-based electrolyte provided more relevant antibacterial effects but did not support cell proliferation. In conclusion, it should be noted that PEO of Mg alloy in silicate baths containing Ca(OH)2 provided the formation of stable biocompatible oxide coatings that could be used in the development of commercial degradable implants.
Keywords: magnesium; plasma electrolytic oxidation; silicate bath; degradation rate; biocompatibility; antibacterial properties